Biogenic activated carbons from conservation grassland biomass for organic micropollutants removal in municipal wastewater - Korbinian Kaetzl; Marcel Riegel; Ben Joseph; Ronja Ossenbrink; Helmut Gerber; Willis Gwenzi; Tobias Morck; David Laner; Thomas Heinrich; Volker Kromrey; Kevin Friedrich; Michael Wachendorf; et al. (Environmental Science and Ecotechnology)
Activated carbons (ACs) are widely used in advanced wastewater treatment to remove organic micropollutants (OMPs), including pharmaceuticals, that evade conventional biological processes. Yet, fossil coal-based ACs generate substantial CO2 emissions and conflict with circular-bioeconomy objectives. Here, we address the critical research gap in sustainable sorbent development by evaluating biogenic ACs produced from underutilized grassland biomass. Using a pretreatment to enrich carbon content and reduce minerals, we generated biogenic ACs from wet meadow (WET) and orchard meadow residues and compared them to Norit SAE Super and PULSORB WP 235 in batch adsorption tests. Despite its higher mineral and ash contents and lower specific surface area than conventional ACs, 100 %-activated WET (WET100) combined balanced micro- and mesoporosity—yielding heterogeneous adsorption sites that conform to Freundlich isotherms—and achieved 50 % OMP removal at a dosage of ∼13 mg L−1, on par with Norit SAE Super (∼12 mg L−1). Strong correlations between OMP removal and ultraviolet absorbance at 254 nm (UVA254; R2 > 0.95) validate UVA254 as a rapid monitoring proxy. Greenhouse gas footprint analyses revealed that substituting coal-based AC with WET100 reduces gate-to-grave emissions by approximately 2.4 t CO2e per tonne of sorbent—translating to potential savings of up to 94 % CO2e when deployed at scale for advanced OMP removal. These findings underscore that biogenic ACs can be seamlessly integrated into existing treatment infrastructure, valorize underutilized grassland biomass, align with circular-economy and EU sustainability objectives, and deliver substantial greenhouse-gas savings compared to coal-based adsorbents.